Promoting Caregiver Mastery in Black American Dementia Caregivers. (5th October 2021) - Bonds Johnson, Kalisha; Brewster, Glenna S; Cicero, Ethan; Hepburn, Kenneth; Clevenger, Carolyn K; Daniel, Gaea; Pak, Victoria; Paul, Sudeshna; Epps, Fayron
Abstract: Over 6 million older Americans live with Alzheimer's disease and related dementias; Black American older adults' prevalence is more than twice that of non-Hispanic White older adults. The Black American dementia caregiving experience can be encapsulated within the Black Family Socioecological Context Model, which provides a conceptual basis for examining social determinants of health at individual, family, community, and societal levels with careful consideration for how the intersection of race, gender, and class of Black American dementia caregivers influences the multiple dimensions of their caregiving experiences. Family dynamics, community setting, and health care systems have a potentially bidirectional influence on these caregivers, which is shaped by historical and ongoing systemic and institutional racism and general disenfranchisement. This Forum article outlines how the Social Cognitive Theory offers ways for Black American dementia caregivers to achieve a sense of mastery within the complicated and fraught ecology within which their caregiving occurs. We propose a research agenda to create programs and interventions for enhancing a sense of mastery among Black American dementia caregivers. Two concepts in particular, "constraints" and "efficacy expectations, " provide ways to create a systematic approach to developing successful coping strategies for the constraints perceived by individuals as they undertake and function in the caregiving role. The recognition of the complexity of the caregiving ecosystem and intersectionality of caregivers' experience and identity emphasize the importance of individualization: Each caregiver's experience of this ecosystem—and therefore each Black American dementia caregiver's way to mastery within it—will be uniquely shaped and experienced.